RECYCLING OF RADIOACTIVE METALS FROM SECONDARY RAW MATERIALS - Kolobov , German; Pecheritsa , Alexander; Bubsnets , Aleksey; Prokhorova , Nastasia (Scientific Journal "Metallurgy", 2020)
Radioactive and other metals can be obtained from waste products and waste from the nuclear industry. In the processing of spent nuclear fuel and other types of waste, hydrometallurgical technologies are used to extract uranium, thorium, plutonium, technetium, americium, rare earth elements, cesium, zirconium and rhenium. This report provides an overview of new (2016-2018) publications devoted mainly to the reprocessing of spent nuclear fuel and the production of molybdenum-99 radionuclide. Methods of processing spent nuclear fuel of nuclear power plants can be classified into water and non-water. Currently, only the hydrometallurgical technology for the processing of spent nuclear fuel from thermal reactors, the socalled PUREX process, which is based on liquid extraction using tributylphosphate, has been implemented on an industrial scale. The authors patented an extraction mixture and a method for extracting and from a highly active raffinate of spent nuclear fuel processing. The procedure for applying extraction processes at the Siberian Chemical Combine includes the choice of extracting, calculation of the extraction process, and equipment selection. The prospects for reprocessing spent nuclear fuel based on the uranium-thorium alloy are considered in known work. To isolate thorium and rare-earth metals from radioactive residues, Cyanex 572 extracting dissolved in kerosene was tested. The method of processing irradiated nuclear fuel, proposed, involves the autoclave dissolution of spent nuclear fuel in nitric or hydrochloric acid at a temperature of 400-500 ºС and a pressure of 30-40 MPa. The problem of SNF reprocessing by the electrochemical method using the FFC Cambridge process is known. To improve the extraction processes, a new activating additive, (CF3SO2) 2NSi, was proposed, which makes it possible to extract cesium with sufficiently high distribution coefficients from neutral solutions. To extract americium from spent nuclear fuel and purify it from plutonium and uranium in the patent it was proposed to use electrolysis in molten chloride salts with liquid electrodes from cadmium or bismuth. The main operations of the uranium extraction technology proposed. The technology for processing zirconium-containing intermediate product of uranium